Enhancing solar steam generation through manipulating the heterostructure of PVDF membranes with reduced reflection and conduction. Issue 29 (10th July 2019) - Li, Tiantian; Fang, Qile; Lin, Haibo; Liu, Fu
Abstract : A distillation device integrates key functions e.g. self-floating, self-insulating, self-water drawing and steam transpiration in one piece of a PVDF/AuNP membrane. Abstract : Solar steam generation has recently attracted intense attention due to its high solar energy efficiency. However, the state-of-the-art solar distillators are usually composed of solar absorption, water supply and thermal insulation accessories separately, which complicate the fabrication and utilization of the device. Here, a thin polymeric membrane with an asymmetric structure and asymmetric wettability is fabricated for simplifying the vapour generation device. The simplified membrane can integrate enhanced solar harvesting, insulating, water drawing, steam transpiration and self-floating properties in a piece of a polyvinylidene fluoride (PVDF) membrane. The top hydrophilic layer loaded with gold nanoparticles (AuNPs) or carbon black (CB) exhibits enhanced broadband light absorption due to the synergistic effect of AuNPs (or CB) and water. The bottom hydrophobic layer facilitated the heat confinement via reducing the heat conduction and minimizing the water pathway through a round edge. This integrative PVDF membrane shows superior performances compared with traditional complex solar steam generation devices. The simplified thin-film distillator allows us to reclaim purified water without recourse to any other accessories, e.g. insulating foam, water path paper or support.